How talent management execution impacts career experiences: exploring the organization-individual intersect - van der Merwe, Marna; Nel, Petrus; Hoole, Crystal (Frontiers in Psychology, 2024)
The aim of the research was to investigate the ways in which talent management execution impacts the individual career experiences of talent, specifically exploring how talent management execution and career enablement can be closer aligned to unlock value for both the organization and the individual. A qualitative research design was employed to explore the research question. During the first phase of the research data was collected from 13 talent management professionals using purposeful sampling and semi-structured interviews. During the second phase of the research the Delphi method was used to validate the findings (n = 8). Four broad themes were identified as the most prominent ways in which talent management execution impacts the career experiences of individuals. The first is the philosophical underpinning that the organization holds in how talent is defined as well as the exclusivity or inclusivity of their approach. The second is the identification criteria used to identify talent within the organization. Thirdly, the extent to which talent management practices are aligned with career enablement practices and the congruence between these. Lastly, the role of the psychological contract and employee experience in managing mutual expectations. The resultant tension must be proactively managed by (1) clearly articulating the talent philosophy and making this visible through talent management execution, (2) ensuring alignment between talent management practices and the career enablement available to talent, and (3) delivering on expectations through the lived experiences of talent. The study contributes to the existing body of knowledge on talent management and careers, with a specific focus on the intersection between these and defining ways to align these practices to create congruent and authentic career experiences for individuals.